UJI KECERNAAN CORN GLUTEN MEAL DAN CORN STEEP POWDER SEBAGAI BAHAN BAKU PAKAN IKAN BANDENG (Chanos chanos) - Danu Ramadana; Achmad Noerkhaerin Putra; Mas Bayu Syamsunarno (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2022)
Corn Gluten Meal (CGM) and Corn Steep Powder (CSP) are corn-based feed raw materials that have the potential to be used as raw materials for milkfish feed. The purpose of this study was to evaluate the digestibility value of CGM and CSP as raw materials for milkfish feed. Milkfish weighing 7.6±0.684 g was stocked into 12 aquariums measuring 60 cm x 40 cm x 40 cm and the water volume was 15 liters. The study consisted of 3 different types of feeding and 3 replications, namely: K: Reference feed (control), A: CGM test feed and B: CSP test feed. The results showed that the use of CGM and CSP as feed raw materials did not effect on feed intake, specific growth rate and feed efficiency of milkfish. The CGM and CSP test feeds resulted in lower nutrient digestibility values compared to the reference feed. CGM and CSP were not effectively used as raw material for milkfish feed.